Linking the Puzzle Pieces of the Past: A Study of Relational Memory in Children with Autism Spectrum Disorder. Issue 11 (1st September 2020) - Mogensen, Rasmine L. H.; Hedegaard, Maja B.; Olsen, Ludvig R.; Gebauer, Line
Abstract: Our memories are made of detailed sensory information representing the puzzle pieces of our personal past. The type of memory integrating sensory features is referred to as relational memory. The main objective of this study was to investigate whether relational memory is affected in children with autism spectrum disorder (ASD) since altered relational memory may contribute to atypical episodic memory observed in ASD. We also examined the association between perceptual style and relational memory abilities. Children with ASD ( n = 14) and typically developed (TD) children ( n = 16, 9–15 years old) completed a memory task with three conditions: two single‐feature conditions measuring memory for objects and locations, and one relational memory condition measuring memory for objects and their locations combined. The Children's embedded figures test was administered to measure perceptual style. The ASD group selected more incorrect stimuli (false alarms) than the TD group, resulting in a lower proportion of correctly recognized targets across all memory conditions. The ASD group did not display a more local perceptual style than the TD group. However, perceptual style was associated with improved memory abilities across conditions. Our findings indicate that the overall memory performance of children with ASD is less stable, leading them to more incorrect responses than TD children. This may be due to the executive demands of the memory tasks, rather than specific impairments in memory binding. Autism Res 2020, 13 : 1959‐1969. © 2020 International Society for Autism Research and Wiley Periodicals LLC Lay Summary: The present study shows that children with autism have a less stable memory than typically developed children, which is reflected in a higher amount of incorrect memory responses. Overall, our results indicate that children with autism display difficulties in differentiating previously studied from novel information when solving both single‐feature memory tasks and a relational memory task (requiring memory of combination of features). These difficulties may have implications for how children with autism remember episodes from their personal past.